Correlation of Age, Nutritional Status, and Smoking Habits with Work Fatigue in Dome Installation Workers - Tazkia Salsabila; Mulyono Mulyono (Universitas Airlangga, 2021)
Introduction: All works have the potential to cause work fatigue, one of which is in the dome installation work. Work fatigue leads to decreased work capacity and endurance to work. Factors causing work fatigue are age, sex, nutritional status, smoking habits, history of illness, work environment, workload, work hours, and rest periods. This study aims to find out the correlation between age, nutritional status, and smoking habits with work fatigue in dome installation workers at PT. A. Methods: This type of research was an observational analytic research using a cross-sectional approach. This study had a population of all employees of PT. A in the dome installation section. The samples used were 33 workers, taken using total sampling. This study was conducted in 2020. This study used variables of age, nutritional status, smoking habits, and work fatigue. Instrument for collecting data was a questionnaire. The Industrial Fatigue Research Committee (IFRC) questionnaire was specifically used to collect data on work fatigue. In addition, data on nutritional status were obtained from the calculation of Body Mass Index (BMI). The contingency coefficient was used to analyze the data. Results: Theworkers mostly (81.8%) experienced mild work fatigue and were aged ≤ 35 years, had normal nutritional status, and were mild smokers. Conclusion: There was a weak relationship between age and nutritional status with work fatigue and a veryweak relationship between smoking habits with work fatigue. Keywords: age, nutritional status, smoking habits, work fatigue